###### Advertisements

###### Advertisements

Sum

**Simplify : **(7x – 8) (3x + 2)

###### Advertisements

#### Solution

(7x – 8) (3x + 2) = 7x(3x + 2) −8(3x+ 2)

= 21x^{2} + 14x – 24x – 16

= 21x^{2} – 10x – 16

Concept: Multiplying a Polynomial by a Polynomial

Is there an error in this question or solution?

#### APPEARS IN

#### RELATED QUESTIONS

**Multiply:** 5p^{2 }+ 25pq + 4q^{2} by 2p^{2} − 2pq +3q^{2}

**Simplify : **(px – q) (px + q)

**Simplify : **(4x – 5y) (5x – 4y)

The adjacent sides of a rectangle are x^{2} – 4xy + 7y^{2} and x^{3} – 5xy^{2}. Find its area.

The base and the altitude of a triangle are (3x – 4y) and (6x + 5y) respectively. Find its area.

Multiply -4xy^{3} and 6x^{2}y and verify your result for x = 2 and y= 1.

Find the value of (3x^{3}) × (-5xy^{2}) × (2x^{2}yz^{3}) for x = 1, y = 2 and z = 3.

Evaluate (x^{5}) × (3x^{2}) × (-2x) for x = 1.

**Evaluate: **(2x – 5y)(2x + 3y) for x = 2 and y = 3.

**Evaluate: **xy^{2}(x – 5y) + 1 for x = 2 and y = 1.